2013
DOI: 10.1097/hnp.0b013e31828b6270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Guided Imagery Intervention on Stress in Hospitalized Pregnant Women

Abstract: Using repeated-measures pre-/posttest design, the effects of guided imagery on maternal stress in 19 hospitalized pregnant women were examined. Mean stress and systolic blood pressure measurements postintervention were significantly lower than mean levels before listening to the guided imagery CD. All participants identified benefits of this holistic intervention. The study provides preliminary evidence that a guided imagery intervention may be effective in reducing maternal stress in hospitalized pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Guided imagery has been shown to decrease stress in women with fibromyalgia [11], hospitalized pregnant women [33], and patients with inflammatory bowel disease [34]. Kolcaba and Fox reported that guided imagery was effective at increasing the comfort of women undergoing radiation therapy for early stage breast cancer, especially in the first three weeks of therapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Guided imagery has been shown to decrease stress in women with fibromyalgia [11], hospitalized pregnant women [33], and patients with inflammatory bowel disease [34]. Kolcaba and Fox reported that guided imagery was effective at increasing the comfort of women undergoing radiation therapy for early stage breast cancer, especially in the first three weeks of therapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, this population was found to have lower state anxiety scores but not perceived stress scores compared to control group immediately after 3 sessions and over time until delivery [32]. Women hospitalized with preterm labor in the US reported significantly lower mean perceived stress levels after listening to a GI intervention compared to preintervention stress levels [33]. However, background music was added to the GI, thus making it difficult to isolate the effect of imagery.…”
Section: Introductionmentioning
confidence: 99%
“…We adapted the wording and some of the examples to suit mothers with low educational levels, using specific guidelines for Dutch texts [61], and the input of several nurses who work as home visitors for Supportive Parenting. Guided imagery relaxation exercises like these can positively affect both perceived stress and physiological stress in a range of populations (e.g., [23,62,63]). Listening to guided imagery exercises has also shown to decrease levels of anxiety and pain in hospital settings, for example prior to surgery [64].…”
Section: Reducing Levels Of Perceived Stressmentioning
confidence: 99%